Negative electrode sheet and battery

CN122889697APending Publication Date: 2026-10-09ZHUHAI COSMX BATTERY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610945339.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-06-26
Publication Date
2026-10-09

AI Technical Summary

Technical Problem

[0003]然而,硅碳材料在充放电过程中存在显著的体积膨胀和锂枝晶析出问题,导致电极结构粉化、SEI膜反复破裂以及电池循环寿命缩短,严重限制了其商业化应用

Benefits of technology

[0048]本申请通过双层负极结构设计与多维度材料优化,解决硅碳负极的膨胀与安全风险问题。具体而言,发明人提出通过第二负极活性层硅碳材料的几何结构优化(消除尖角以降低隔膜刺穿风险)、固态电解质的界面修饰(形成机械约束并促进锂离子均匀嵌入)、第一负极活性层以及第二负极活性层中石墨的差异化选择的协同作用,实现对硅碳负极膨胀行为的系统性抑制,同时提升电池的能量密度、循环寿命与安全性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122889697A_ABST
    Figure CN122889697A_ABST
Patent Text Reader

Abstract

This application provides a negative electrode sheet and a battery. The negative electrode sheet includes a negative electrode current collector, a first negative electrode active layer, and a second negative electrode active layer stacked sequentially; the first negative electrode active layer includes a first graphite, and the second negative electrode active layer includes a second graphite, a silicon-carbon material, and a first solid electrolyte; the peak intensity I of the first graphite is... G With peak intensity I D The peak intensity I of the second graphite G 'With peak intensity I D 'Satisfy: I D / I G >I D ' / I G The silicon-carbon material includes spherical silicon-carbon material; all angles in the cross-section of the spherical silicon-carbon material on the surface of the second negative electrode active layer away from the negative electrode current collector are >120°. The battery including this negative electrode sheet has both higher energy density and cycle capacity retention, while also exhibiting lower cycle expansion rate.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of electrochemical technology, and in particular to a negative electrode and a battery. Background Technology

[0002] Lithium-ion batteries, as high-energy-density energy storage devices, have been widely used in electric vehicles, energy storage systems, consumer electronics (such as smartphones and laptops), and aerospace. With the rapid development of the new energy industry, the market is placing higher demands on the energy density of lithium-ion batteries. Silicon-carbon materials, due to their high theoretical specific capacity (far exceeding that of graphite), are considered ideal anode materials for next-generation high-energy-density lithium-ion batteries.

[0003] However, silicon-carbon materials exhibit significant volume expansion and lithium dendrite deposition during charge and discharge, leading to electrode structure pulverization, repeated SEI film rupture, and shortened battery cycle life, severely limiting their commercial application. Particularly in high-silicon content anodes, localized stress concentration and uneven lithium-ion transport further exacerbate the risks of expansion and lithium plating. Furthermore, with the increase in battery energy density, consumers are placing more stringent demands on battery safety (such as short-circuit risk) and long-term stability (such as high-temperature cycling performance).

[0004] Therefore, developing novel silicon-carbon anode sheets that combine high energy density, low expansion rate, and excellent cycle stability has become a critical issue that the industry urgently needs to address. Summary of the Invention

[0005] This application provides a negative electrode and a battery. The battery including the negative electrode has both higher energy density and cycle capacity retention rate, while having a lower cycle expansion rate.

[0006] This application provides a negative electrode sheet, wherein the negative electrode sheet includes a negative electrode current collector, a first negative electrode active layer and a second negative electrode active layer;

[0007] The first negative electrode active layer is located on at least one side surface of the negative electrode current collector, and the second negative electrode active layer is located on the surface of the first negative electrode active layer away from the negative electrode current collector;

[0008] The first negative electrode active layer includes a first active material, which includes a first graphite; the second negative electrode active layer includes a second active material and a first solid electrolyte, which includes a second graphite and a silicon-carbon material.

[0009] In the Raman spectrum, the first graphite is at a wavelength of 1530 cm⁻¹. -1 ~1590cm -1 Peak intensity I G With a wavelength of 1330cm -1~1390cm -1 Peak intensity I D The second graphite at a wavelength of 1530 cm -1 ~1590cm -1 Peak intensity I G 'With wavelength 1330cm -1 ~1390cm -1 Peak intensity I D 'Satisfy: I D / I G >I D ' / I G ';

[0010] The silicon-carbon material includes spherical silicon-carbon material; all angles in the cross-section of the spherical silicon-carbon material on the surface of the second negative electrode active layer away from the negative electrode current collector are >120°.

[0011] The negative electrode as described above, wherein 0.2 ≤ I D ' / I G ≤0.8; preferably, 0.2≤I D ' / I G ≤0.6;

[0012] And / or, 0.2≤I D / I G ≤0.95; preferably, 0.3≤I D / I G ≤0.9;

[0013] And / or, the Dv50 of the first graphite is 3-10 μm;

[0014] And / or, the Dv50 of the second graphite is 8-20 μm;

[0015] And / or, the mass percentage of silicon in the spherical silicon-carbon material is A, and the mass percentage of silicon-carbon material in the second active material is B, where 0.45 ≤ A / B ≤ 2.1;

[0016] Preferably, A is 30%-70%; and / or, B is 20%-70%;

[0017] Preferably, the silicon-carbon material comprises a porous carbon framework and silicon particles located in the pores of the porous carbon framework.

[0018] The negative electrode sheet as described above, wherein the first solid electrolyte comprises at least one of Al, Ti, and La;

[0019] Preferably, the first solid electrolyte comprises at least one of lithium aluminum titanium phosphate, lithium lanthanum titanate, and lithium lanthanum zirconium oxide.

[0020] And / or, in the second negative electrode active layer, the mass percentage content of the first solid electrolyte is 1%-5%;

[0021] Preferably, when the first solid electrolyte comprises lithium aluminum titanium phosphate and the second negative electrode active layer comprises aluminum, the mass ratio of aluminum to silicon is 0.03% to 0.15%.

[0022] Preferably, when the first solid electrolyte includes at least one of lithium aluminum titanium phosphate and lithium lanthanum titanate, the second negative electrode active layer includes titanium, and the mass ratio of titanium to silicon is 0.4% to 2.1%;

[0023] Preferably, in the second negative electrode active layer, when the first solid electrolyte includes at least one of lithium lanthanum titanate and lithium lanthanum zirconium oxide, the second negative electrode active layer includes lanthanum, and the mass ratio of lanthanum to silicon is 0.05% to 0.4%.

[0024] The negative electrode as described above, wherein the spherical silicon-carbon material comprises a silicon-carbon matrix and a carbon layer located on at least a portion of the surface of the silicon-carbon matrix; and / or,

[0025] At least a portion of the surface of the spherical silicon-carbon material is coated with the first solid electrolyte, and the ratio of the Dv50 of the spherical silicon-carbon material to the Dv50 of the first solid electrolyte is 20 to 200; preferably, the ratio of the Dv50 of the spherical silicon-carbon material to the Dv50 of the first solid electrolyte is 20 to 107; preferably, the Dv50 of the spherical silicon-carbon material is 1 μm to 20 μm; preferably, the Dv50 of the first solid electrolyte is 10 nm to 1000 nm.

[0026] And / or, the ratio of the porosity of the first negative electrode active layer to the porosity of the second negative electrode active layer is 1-1.9; preferably, the first negative electrode active layer includes a lithium replenishing agent; preferably, the lithium replenishing agent includes lithium powder; preferably, the mass percentage of the lithium replenishing agent in the first negative electrode active layer is 0.5%-5%, more preferably 0.6%-3%; and / or,

[0027] The first negative electrode active layer includes a first additive, and the second negative electrode active layer includes a second additive; the first additive and / or the second additive includes at least one of a binder, a conductive agent, and a dispersant; the ratio of the mass percentage of the second additive in the second negative electrode active layer to the mass percentage of the first additive in the first negative electrode active layer is 1.5-5.

[0028] The negative electrode sheet as described above, wherein the surface of the second negative electrode active layer away from the negative electrode current collector has N first recesses, where N≥1;

[0029] Preferably, the distance between two adjacent first recesses is 0.1 μm-5 μm;

[0030] Preferably, the depth of the first recess is 0.1 μm-25 μm;

[0031] Preferably, the first recess has a dimension of 20μm-200μm along the length of the negative electrode sheet.

[0032] This application also provides a battery, which includes a negative electrode as described above.

[0033] The battery as described above further includes a positive electrode sheet, the positive electrode sheet including a positive current collector and a positive active layer located on at least one side surface of the positive current collector, the positive active layer including a second solid electrolyte;

[0034] Preferably, the second solid electrolyte comprises at least one of garnet-type solid electrolyte, perovskite-type solid electrolyte, and sulfide solid electrolyte; preferably, the second solid electrolyte comprises at least one of lithium aluminum titanium phosphate, lithium lanthanum titanate, and lithium lanthanum zirconium oxide.

[0035] Preferably, in the positive electrode active layer, the mass percentage of the second solid electrolyte is 0.01%-0.1%;

[0036] Preferably, the ratio of the Dv50 of the spherical silicon-carbon material to the Dv50 of the second solid electrolyte is 20 to 200; preferably, the ratio of the Dv50 of the spherical silicon-carbon material to the Dv50 of the second solid electrolyte is 20 to 107; preferably, the Dv50 of the second solid electrolyte is 10 to 1000 nm.

[0037] In the battery described above, the positive electrode active layer further includes a positive electrode active material, the positive electrode active material includes lithium cobalt oxide, the lithium cobalt oxide includes element M, and element M includes Y and / or La;

[0038] Preferably, in the lithium cobalt oxide, the mass percentage of element M is 0.005%-0.6%;

[0039] Preferably, the M element includes Y, and the mass percentage of Y element in the lithium cobalt oxide is 0.005%-0.3%;

[0040] Preferably, the M element includes L, and the mass percentage of La element in the lithium cobalt oxide is 0.005%-0.3%.

[0041] In the battery described above, the surface of the positive electrode active layer away from the positive electrode current collector has Q second recesses, where Q ≥ 1;

[0042] Preferably, the distance between the center points of two adjacent second recesses is 100μm-2000μm;

[0043] Preferably, the width of the second recess is 6μm-150μm;

[0044] Preferably, the depth of the second recess is 3μm-25μm;

[0045] Preferably, the battery has a wound structure, and the positive electrode sheet includes a straight section and a bent section along the winding direction. The positive electrode active layer of the bent section has Q' second recesses Q'≥1.

[0046] The battery as described above further includes an electrolyte, said electrolyte comprising fluoroethylene carbonate;

[0047] Preferably, the electrolyte contains 5-18% fluoroethylene carbonate by mass; more preferably, the electrolyte contains 8-18% fluoroethylene carbonate by mass.

[0048] This application addresses the expansion and safety risks of silicon-carbon anodes through a dual-layer anode structure design and multi-dimensional material optimization. Specifically, the inventors propose a synergistic approach that utilizes the geometric structure optimization of the silicon-carbon material in the second anode active layer (eliminating sharp corners to reduce the risk of separator puncture), interface modification of the solid electrolyte (forming mechanical constraints and promoting uniform lithium-ion insertion), and the differentiated selection of graphite in the first and second anode active layers to systematically suppress the expansion behavior of silicon-carbon anodes, while simultaneously improving the battery's energy density, cycle life, and safety. Attached Figure Description

[0049] The accompanying drawings, which are incorporated in and form part of this specification, illustrate embodiments consistent with this application and, together with the description, serve to explain the principles of this application.

[0050] Figure 1 Here are cross-sectional SEM images of the negative electrode sheet in some embodiments of this application;

[0051] Figure 2 for Figure 1 A schematic diagram of the structure of a medium-sized spherical silicon-carbon material;

[0052] Figure 3 This is a schematic diagram of the positive electrode sheet from one perspective in some embodiments of this application;

[0053] Figure 4This is a schematic diagram of the positive electrode sheet from another perspective in some embodiments of this application;

[0054] Figure 5 This is the Raman spectrum of the negative electrode in Embodiment 1 of this application;

[0055] Figure 6 This is a Raman spectral diagram of the graphite in the negative electrode sheet in Embodiment 1 of this application.

[0056] Explanation of reference numerals in the attached figures:

[0057] 11: Negative electrode current collector;

[0058] 12: Negative electrode active layer;

[0059] 21: Positive current collector;

[0060] 22: Positive electrode active layer;

[0061] 221: Second recess. Detailed Implementation

[0062] Exemplary embodiments will now be described in detail, examples of which are illustrated in the accompanying drawings. When the following description relates to the drawings, unless otherwise indicated, the same numbers in different drawings denote the same or similar elements. The embodiments described in the following exemplary embodiments do not represent all embodiments consistent with this application. Rather, they are merely examples of apparatuses and methods consistent with some aspects of this application as detailed in the appended claims.

[0063] How to balance anode capacity improvement, expansion suppression, and safety enhancement in high-energy-density lithium-ion batteries has become an urgent technical problem to be solved. To address this issue, this application combines graphite material configuration with silicon-carbon material morphology control to achieve a more ordered lithium intercalation response and lower mechanical damage risk between different anode active layers, thereby providing a foundation for reducing expansion, suppressing internal short circuits, and improving cycle stability.

[0064] In this application, the length direction is the x-direction, the width direction is the y-direction, and the thickness direction is the z-direction. It can be understood that the length direction of the negative electrode is the same as the length direction of the positive electrode, and winding the stacked positive and negative electrode sheets along their length directions can form a wound battery structure.

[0065] Figure 1 Here are cross-sectional SEM images of the negative electrode sheet in some embodiments of this application. For example... Figure 1As shown, a first aspect of this application provides a negative electrode sheet, which includes a negative electrode current collector 11, a first negative electrode active layer, and a second negative electrode active layer (the negative electrode active layer 12 includes the first negative electrode active layer and the second negative electrode active layer); the first negative electrode active layer is located on at least one side surface of the negative electrode current collector 11, and the second negative electrode active layer is located on the surface of the first negative electrode active layer away from the negative electrode current collector 11; the first negative electrode active layer includes a first active material, which includes a first graphite; the second negative electrode active layer includes a second active material and a first solid electrolyte, which includes a second graphite and a silicon-carbon material;

[0066] In the Raman spectrum, the first graphite is at a wavelength of 1530 cm⁻¹. -1 Up to 1590cm -1 Peak intensity I G (G-band peak intensity) and at a wavelength of 1330cm -1 Up to 1390cm -1 Peak intensity I D (D-band peak intensity), the second graphite at a wavelength of 1530 cm⁻¹ -1 Up to 1590cm -1 Peak intensity I G 'With wavelength 1330cm -1 Up to 1390cm -1 Peak intensity I D 'Satisfy I D / I G >I D ' / I G '; Silicon-carbon materials include spherical silicon-carbon materials; all angles in the cross-section of the spherical silicon-carbon materials on the surface of the second negative electrode active layer away from the negative electrode current collector 11 are greater than 120°.

[0067] This application improves lithium-ion absorption by adding a first solid electrolyte to the second negative electrode active layer, allowing for faster introduction of lithium ions into the first negative electrode active layer. The second graphite in the second negative electrode active layer... D ' / I G The smaller size can solve the problem of large expansion when the silicon-carbon material is fully charged in the second negative electrode active layer, achieving a significant reduction in expansion at both room temperature and high temperature. By using specific spherical silicon-carbon material in the second negative electrode active layer, the problem of poor K value caused by high silicon-carbon material content in the second negative electrode active layer is solved, preventing sharp corners from piercing the separator and connecting to the positive electrode, thus achieving a reduction in K value.

[0068] In this embodiment, the negative electrode current collector 11 can be a commonly used metal conductive substrate for lithium-ion battery negative electrodes, such as electrolytic copper foil, rolled copper foil, or composite copper foil. Preferably, a copper foil with a thickness of 4μm to 20μm is used to balance electronic conductivity, mechanical strength, and adaptability to winding or stacking processes. The first negative electrode active layer can be directly coated on one and / or both sides of the negative electrode current collector 11, serving as a support layer, conductive layer, or buffer layer near the negative electrode current collector 11. The second negative electrode active layer is further disposed on the surface of the first negative electrode active layer away from the negative electrode current collector 11, thus forming a surface active layer facing the separator. This layered arrangement is not a simple material stacking, but rather a differentiated configuration of the microstructure and lithium intercalation behavior of the active materials at different layers. This prioritizes conductivity continuity and structural load-bearing capacity on the side near the negative electrode current collector 11, while prioritizing high capacity and interface stability on the side near the separator, thereby balancing energy density, thickness expansion suppression, and safety in a high-silicon system. For example, the first negative electrode active layer and the second negative electrode active layer can be formed sequentially by a continuous double-layer coating process, or by a drying-then-coating, wet-on-wet coating, multi-level slit die coating or segmented stacked coating method; in one possible embodiment, there may also be a micro-transition region between the two layers, so that the slurry interface partially interpenetrates, thereby reducing the risk of interlayer delamination and improving the cross-layer transport of electrons and lithium ions.

[0069] Specifically, the first negative electrode active layer includes a first graphite, which may include natural graphite, artificial graphite, mesophase carbon microsphere graphitized material, or a combination thereof, preferably a graphite material with a moderate degree of graphitization and certain surface active sites. The second negative electrode active layer includes a second graphite, silicon-carbon material, and a first solid electrolyte. The second graphite may be graphite with good conductivity, high crystallinity, and good cycle stability. The first solid electrolyte is used to establish a more uniform ion migration pathway and local mechanical buffer structure around the silicon-carbon particles, at the interface between the graphite and silicon-carbon material, and throughout the entire second negative electrode active layer. Based on the above material combination, it can be seen that the first negative electrode active layer mainly undertakes the functions of framework support, stress transmission, and current collection, while the second negative electrode active layer mainly undertakes the functions of capacity contribution and interface regulation. The second graphite and silicon-carbon material form a composite lithium storage host, and the first solid electrolyte reduces the repeated tearing effect of local volume changes on the interface film during silicon lithium insertion and extraction by dispersing between particles, attaching to the surface of the silicon-carbon material, or coating the outer periphery of the silicon-carbon material, so that the high-silicon layer still has acceptable structural integrity during operation. For example, the second negative electrode active layer may further include a binder, a conductive agent, a dispersant, and a thickener. The binder may be selected from styrene-butadiene rubber, sodium carboxymethyl cellulose, polyacrylic acid, alginate, polyimide, or a compound system thereof. The conductive agent may be selected from conductive carbon black, carbon nanotubes, graphene, or vapor-grown carbon fibers, so that the second negative electrode active layer can still maintain good coating film formation and circulating conductive network under silicon-containing conditions. In one possible embodiment, the amount of binder in the second negative electrode active layer may be higher than that in the first negative electrode active layer to enhance the surface layer's ability to constrain silicon expansion.

[0070] Regarding the Raman spectral characteristics of the first graphite and the second graphite, embodiments of this application define the I of the first graphite. D / I G I greater than the second graphite D ' / I G This achieves an ordered configuration of defect features in two layers of graphite. Among them, I... D The first graphite at 1330cm -1 Up to 1390cm -1 Peak intensity of peak D within the range, I G The first graphite at 1530cm -1 Up to 1590cm -1 Peak intensity of G within the range, I D / I G It can characterize the degree of defects, the number of edge sites, and the level of local disorder in graphite materials; correspondingly, I D 'and I G 'These are the peak intensities of the D and G peaks of the second graphite in the same wavenumber range, respectively.' D ' / I G'Used to characterize the defect features of the second graphite. By making the first graphite satisfy a higher I...' D / I G The value indicates that the graphite near the negative electrode current collector 11 has relatively more defect sites, higher surface activity, and stronger interfacial wetting ability, which is beneficial for electrolyte wetting and lithium-ion insertion initiation in the lower layer; while the second graphite has a relatively lower I value. D ' / I G A higher Ig value indicates a higher degree of graphitization, a more complete layered structure, and a more stable electronic conduction path, making it more suitable for co-forming a high-capacity surface system with silicon-carbon materials. The reaction mechanism lies in the fact that the higher-defect graphite in the first negative electrode active layer can provide more accessible lithium storage sites and absorb some of the stress transmitted from the surface layer during the initial charging stage, making the distribution of lithium ions in the thick electrode direction more gradual and reducing local oversaturation of lithium intercalation in the surface layer; the higher-graphitized second graphite in the second negative electrode active layer provides a more stable electronic framework and a lower-resistance parallel transport network for silicon-carbon materials, thereby mitigating the conduction interruption caused by local expansion of silicon. Through this matching of Raman defect relationships, the lithium intercalation kinetics and stress response in the thickness direction are redistributed, thereby reducing interface cracking, pore structure collapse, and polarization increase caused by the mismatch in lithium storage rates between different layers. For example, the first graphite can obtain higher Ig values ​​through ball milling activation, mild surface oxidation, heat treatment control, particle size sieving, or coating peeling. D / I G The second type of graphite can be obtained with lower I content through high-temperature graphitization, surface densification, or particle shape shaping processes. D ' / I G In one possible embodiment, the first graphite and the second graphite may also originate from the same base graphite raw material, but form Raman spectral differences after undergoing different thermal histories and surface treatments.

[0071] like Figure 1 as well as Figure 2As shown, silicon-carbon material is disposed in the second negative electrode active layer, and all angles (including any outward or inward sharp angles) in the cross-section of the spherical silicon-carbon material in the second negative electrode active layer are greater than 120°. The cross-section in this application is the cross-section of the spherical silicon-carbon material in the surface SEM image of the second negative electrode active layer. It can be understood that the silicon-carbon particles do not have sharp protrusions, edges, or small included angle structures in their cross-sectional contours, but present an overall near-spherical, quasi-spherical, or blunted and smooth appearance. Designing the silicon-carbon material as such a blunted spherical structure can significantly reduce the stress concentration of the silicon-carbon material on the local bonding network and separator interface after rolling, especially during cell winding, stacking, hot pressing, and charging expansion, it can reduce the risk of sharp-cornered particles forming local indentations towards the separator. This process achieves a direct coupling between geometric shape control and safety enhancement. Specifically, by reducing high-curvature areas and sharp contact points on the silicon-carbon material surface, the contact stress between the silicon-carbon material and the surrounding graphite, binder, and first solid electrolyte is shifted from point contact to surface contact or passivated contact. This reduces the likelihood of mechanical puncture of the separator, inducing internal short circuits, and causing severe rupture of the localized SEI (Solid-Induced Deposition) Elec (Ethylene Carbonate) trolyte interphase film. Simultaneously, spherical silicon-carbon materials typically exhibit more uniform anisotropic expansion during lithium intercalation, making them less prone to directional cracking and sharp edge exposure compared to irregular silicon-carbon materials. Therefore, they are more conducive to maintaining the flatness and interface stability of the negative electrode surface under long-cycle and high SOC (State of Charge) conditions. For example, spherical silicon-carbon materials can be prepared by spray granulation followed by sintering and shaping, melt atomization, plasma spheroidization, chemical deposition spheroidization, spheroidization grinding, or secondary agglomeration and shaping. They can also be further coated with carbon, oxide, or solid electrolyte to balance conductivity, interface stability, and expansion constraint.

[0072] The first solid electrolyte introduced in this embodiment can be selected from oxide solid electrolytes, phosphate solid electrolytes, sulfide solid electrolytes, or composites thereof, such as lithium lanthanum zirconium oxide, lithium lanthanum titanium oxide, lithium aluminum titanium phosphate, and phosphate-doped lithium-ion conductors. The first solid electrolyte can be uniformly distributed as independent particles in the second negative electrode active layer, or preferably attached to the surface of spherical silicon-carbon material, or located in the contact area between the second graphite and silicon-carbon material to form a local ion-conducting phase. By introducing a solid electrolyte with lithium-ion transport capability and high mechanical modulus into the surface high-silicon system, on the one hand, the migration path of lithium ions in the second negative electrode active layer can be shortened, the ion flux uniformity between different particles can be improved, and the local enrichment of lithium ions during high-rate charging can be avoided; on the other hand, the inorganic framework properties of the first solid electrolyte itself can also constrain the volume expansion of silicon-carbon material in the lithium-intercalated state, reducing the mutual compression between silicon-carbon materials and the failure of the bonding network. The reaction mechanism lies in the fact that the first solid electrolyte, acting as an ion transport medium and a localized hard phase support, can disperse the strain energy of the silicon-carbon material during charging and discharging, and suppress the opportunity for the liquid electrolyte to directly and extensively contact the nascent silicon surface. This results in a more uniform SEI film formation, thereby reducing lithium loss, impedance growth, and gas expansion caused by repeated SEI rupture and regeneration. For example, the first solid electrolyte can be introduced through in-situ deposition, wet coating, mechanical mixing, spray deposition, sol-gel deposition, or atomic layer deposition.

[0073] At the manufacturing level, the negative electrode sheet of this application embodiment can be formed in the following manner: First, a first negative electrode active layer slurry is prepared by mixing and dispersing first graphite, binder, conductive agent and solvent, preferably using an aqueous system or a mixture of water and organic solvent to obtain suitable viscosity and coating stability; then, the first negative electrode active layer slurry is coated on the surface of the negative electrode current collector 11 and dried to form the first negative electrode active layer. Then, a second negative electrode active layer slurry is prepared by compounding and dispersing second graphite, spherical silicon carbon material, solid electrolyte, binder and conductive agent, and if necessary, by combining low-shear premixing and high-shear homogenization to avoid the spherical silicon carbon material being destroyed and regenerating sharp corners; then, the second negative electrode active layer slurry is coated on the surface of the first negative electrode active layer away from the negative electrode current collector 11 and dried, and finally, a negative electrode sheet including the second negative electrode active layer is obtained by processes such as rolling and slitting. In this process, the rolling pressure and compaction density can be adjusted according to the silicon content of the surface layer to ensure both volumetric energy density and retain the necessary porosity buffer for silicon expansion. In one possible embodiment, the compaction degree of the second negative electrode active layer can be slightly lower than that of the first negative electrode active layer, or expansion accommodation space can be reserved on the surface layer by means of local porosity control, laser micropore construction, etc., so that the double-layer structure can maintain good thickness stability and interlayer adhesion under full charge.

[0074] From the overall working process, when the negative electrode is assembled into a lithium-ion battery and undergoes charging and discharging, lithium ions first contact the second negative electrode active layer from the electrolyte side. Due to the composite network of second graphite, spherical silicon-carbon material, and the first solid electrolyte in the second negative electrode active layer, lithium ions can rapidly distribute on the surface and partially intercalate into the silicon-carbon material and second graphite. Simultaneously, the solid electrolyte makes the local ion flux more uniform, mitigating concentration polarization around the silicon-carbon material. As the lithium intercalation process progresses, the higher Ig content in the first negative electrode active layer... D / I G The first graphite layer, possessing more active defect sites, can continue to accept lithium-ion insertion and provide stress buffering, preventing the lithium concentration gradient along the thicker electrode direction from becoming too steep. Through this layered transport and structural synergy principle, although the surface silicon-carbon material contributes significantly to capacity, the stress caused by its expansion is not concentrated at the separator interface or the tip of a single silicon-carbon material. Instead, it is dispersed through the spherical shape of the silicon-carbon material, the inorganic buffer phase of the first solid electrolyte, and the underlying defective graphite framework. This suppresses the thickness increase of the negative electrode under high SOC, high rate, and long cycle conditions, reduces pulverization, shedding, and localized lithium plating of the first and / or second negative electrode active layers, thereby improving cycle retention, DC internal resistance stability, and internal short-circuit safety margin.

[0075] Based on the above analysis, this application forms a bilayer negative electrode structure that balances electron conduction, ion uniformity, volume change buffering, and membrane safety protection by setting the first graphite near the negative electrode current collector 11 to a relatively high defect characteristic, setting the second graphite on the surface to a relatively high graphitization characteristic, and introducing spherical silicon-carbon material with obtuse-angle geometry and a first solid electrolyte on the surface. This allows for increased negative electrode capacity in high-energy-density lithium-ion batteries while reducing full-charge thickness expansion, mitigating repeated interface film rupture, suppressing local lithium plating, and reducing the risk of internal short circuits. It should be understood that the above examples are merely illustrative and not limiting. Without departing from the concept of this application, the types, proportions, preparation processes, and interlayer transition forms of the first graphite, second graphite, silicon-carbon material, and first solid electrolyte can all be adjusted accordingly, and all such adjustments should fall within the protection scope of the embodiments of this application.

[0076] In some implementations, SEM testing can be performed on the surface of the negative electrode to obtain a surface SEM image of the negative electrode, allowing observation of the degree of all angles in the cross-section of the spherical silicon-carbon material in the surface SEM image; SEM testing can also be performed on the cross-section of the negative electrode to obtain a cross-sectional SEM image of the negative electrode, allowing observation of the composition of the first negative electrode active layer (excluding the spherical particles) and the second negative electrode active layer (including the spherical particles). Figure 1As can be seen, the negative electrode active layer of this application includes a first negative electrode active layer and a second negative electrode active layer, wherein the second negative electrode active layer includes silicon-carbon material ( Figure 1 (Spherical particles in the middle).

[0077] In some implementations, a Raman spectrometer can be used to test the cross-section of the negative electrode. Along the thickness direction of the negative electrode, a scan is performed from the top to the bottom of the cross-section to obtain the Raman spectrum of the first graphite and the Raman spectrum of the second graphite. The Ig of the first graphite is then obtained based on its Raman spectrum. D / I G Based on the Raman spectrum of the second graphite, the I of the second graphite was obtained. D ' / I G '.

[0078] In some implementations, the cross-section of the negative electrode can be subjected to SEM-EDS testing, and the presence of the first solid electrolyte in the second negative electrode active layer can be determined based on the test results.

[0079] In some embodiments, when the monolayer thickness of the first negative electrode active layer is 15 μm–60 μm; and / or the monolayer thickness of the second negative electrode active layer is 10 μm–30 μm, the first negative electrode active layer and the second negative electrode active layer can be more fully matched, thereby improving the electrochemical performance of the battery.

[0080] In one possible implementation, 0.2 ≤ I D / I G When the density is ≤0.95, the graphite layer has a higher degree of graphitization and fewer structural defects, thereby significantly improving electronic conductivity and lithium intercalation capacity, enhancing the interfacial bonding force and electron transport efficiency between the first negative electrode active layer and the negative electrode current collector 11, while increasing the compaction density of the first negative electrode active layer to improve energy density, reducing interfacial impedance growth and side reactions, and working with the second negative electrode active layer to ensure ion transport and fast charging performance, realizing rapid electron conduction inside the negative electrode sheet and structural stability and reliability, thereby improving the overall cycle stability and rate charge and discharge performance of the battery.

[0081] For example, I D / I G It can be a range of any one of 0.2, 0.3, 0.4, 0.6, 0.8, and 0.95, or any two of them. Further, 0.3 ≤ I D / I G ≤0.9.

[0082] In one possible implementation, when the Dv50 of the first graphite is 3-10 μm, it can shorten the diffusion path of lithium ions inside the first negative electrode active layer, improve the electron conduction and ion transport rate of the first negative electrode active layer, reduce the interfacial impedance between the negative electrode current collector 11 and the first negative electrode active layer, and at the same time, the first graphite is more densely packed and has more contact points, which can enhance the overall conductivity and structural adhesion of the negative electrode sheet. In addition, the first graphite can also improve the compaction density and energy density of the first negative electrode active layer, and form a reasonable particle size gradient structure with the second graphite in the second negative electrode active layer, optimize the pore distribution and electrolyte transport channels inside the negative electrode sheet, ensure that the first negative electrode active layer responds quickly to charge and discharge signals, and also take into account the structural stability and low side reactions of the second negative electrode active layer, ultimately achieving a synergistic improvement in battery rate performance, cycle stability and energy density.

[0083] For example, the Dv50 of the first graphite can be a range of any one of 3μm, 5μm, 7μm, 10μm, or any two of them.

[0084] In one possible implementation, 0.2 ≤ I D ' / I G When the content of lithium ions is ≤0.8, the second negative electrode active layer has a more suitable defect content and ion transport channels, which can significantly improve the lithium ion diffusion rate and electrolyte wettability, reduce interfacial polarization and optimize SEI film stability. At the same time, the first negative electrode active layer close to the negative electrode current collector 11 ensures high capacity and electronic conduction efficiency. Ultimately, while improving the battery fast charging performance and suppressing lithium plating, it also takes into account energy density and cycle life, and improves the overall structural stability of the negative electrode sheet.

[0085] For example, I D ' / I G 'It can be a range consisting of any one of 0.2, 0.3, 0.4, 0.6, and 0.8, or any two of them. Further, 0.2 ≤ I D ' / I G ≤0.6.

[0086] In one possible implementation, when the Dv50 of the second graphite is 8-20 μm, the specific surface area of ​​the second graphite is relatively small, which can reduce the degree of side reactions between the second negative electrode active layer and the electrolyte, and is conducive to the formation of a thinner and denser stable SEI film, thereby improving the first coulombic efficiency. At the same time, the second graphite has higher structural integrity and a milder volume effect, which can alleviate particle breakage and electrode expansion during charge and discharge, and improve the structural stability and long-cycle performance of the negative electrode. In addition, it can also improve the overall strength of the second negative electrode active layer, reduce the problem of powder shedding and peeling of the second negative electrode active layer, and, in conjunction with the high conductivity design of the first negative electrode active layer, further improve the battery cycle life and high-temperature storage performance while taking into account a certain ion transport.

[0087] For example, the Dv50 of the second graphite can be a range of any one of 8μm, 9μm, 10μm, 15μm, 20μm, or any two of them.

[0088] In one possible implementation, when the mass percentage of second graphite in the second negative electrode active material is 20%-66.6%, it can increase the proportion of negative electrode active material and effective lithium intercalation capacity in the second negative electrode active layer while ensuring the structural strength of the negative electrode sheet. At the same time, the excellent structural stability of the second graphite itself is used to maintain the density and integrity of the second negative electrode active layer, reducing excessive side reactions of the electrolyte in the second negative electrode active layer. Combined with the efficient conductive network formed by the first graphite in the first negative electrode active layer, it avoids insufficient ion conduction and excessive polarization in the second negative electrode active layer due to too low a second graphite content, and also prevents the negative electrode sheet from becoming less flexible and prone to peeling due to too high a second graphite content. This further balances the energy density, interface stability and cycle life of the battery, while improving the rate response and lithium plating suppression effect during fast charging.

[0089] For example, the mass percentage of the second graphite can be any one of 20%, 21%, 30%, 40%, 50%, 66.6%, or any combination thereof.

[0090] In one possible implementation, the mass percentage of silicon in the spherical silicon-carbon material is A, and the mass percentage of silicon-carbon material in the second active material is B. When 0.45≤A / B≤2.1, the effective active silicon ratio and overall expansion stress level of the second negative electrode active layer can be precisely controlled. While ensuring high specific capacity, it avoids excessive local silicon content, which can lead to concentrated volume effects, electrode cracking and pulverization, and repeated rupture and growth of the SEI film. This ratio can make the expansion behavior of the silicon-carbon material more uniform and controllable, reduce the risk of structural damage to the second negative electrode active layer, improve interface stability and cycle life, and at the same time, work with the second graphite to build a stable ion and electron transport pathway, taking into account both high capacity and rate performance, and achieving synergistic optimization of the structural stability and electrochemical performance of the second negative electrode active layer.

[0091] For example, A / B can be a range consisting of any one of 0.45, 0.5, 0.6, 0.9, 1, 1.5, 2, 2.1 or any two of them.

[0092] Furthermore, when A is 30%-70%, using silicon-carbon materials with higher silicon doping content reduces the lithium-ion transport rate within the silicon-carbon material to address the issue of large expansion at full charge. This allows for direct control of the effective load level of high-capacity silicon in the second negative electrode active layer. This fully leverages the high specific capacity of silicon-carbon materials, improving the overall energy density of the battery, while avoiding excessive silicon content that could lead to severe volume expansion and structural breakage. It also reduces impedance increases and capacity decay caused by repeated SEI film formation. Simultaneously, a reasonable silicon content can form a stable composite conductive network with the second graphite, ensuring rapid lithium-ion transport and alleviating stress concentration, improving electrode structural integrity and cycle stability. It also optimizes the interface characteristics of the second negative electrode active layer, suppressing lithium plating under fast charging conditions, ultimately achieving a synergistic improvement in high capacity, long cycle life, and excellent rate performance.

[0093] For example, A can be a range of any one of 30%, 40%, 50%, 60%, 70%, or any two of them.

[0094] Furthermore, when B is 20%-70%, it can directly stabilize the overall loading level of high-capacity active material in the second negative electrode active layer. This fully utilizes the high lithium intercalation capacity of silicon to improve battery energy density while avoiding significant volume expansion, structural cracking, and continuous side reactions of the SEI film caused by excessive silicon content. At the same time, it can keep the expansion stress of the second negative electrode active layer and the ion transport channels balanced, forming a gradient stress buffer with the first graphite, reducing electrode peeling and pulverization, and improving cycle stability. It can also precisely control the interface impedance, improve polarization and lithium plating problems during fast charging, and achieve a better match between energy density, cycle life, and rate performance.

[0095] For example, B can be a range of any one of 20%, 30%, 40%, 50%, 70%, or any two of them.

[0096] In some implementations, the battery can be discharged to 0% SOC, the negative electrode can be disassembled and removed, soaked in dimethyl carbonate (DMC) solvent for 12 hours, and then rinsed with DMC to remove lithium salts adhering to the electrode. After drying, the surface active layer powder is scraped off using a scraper to obtain the second active layer powder. Heating to 600°C under a nitrogen atmosphere can remove most of the binder, resulting in an intermediate powder containing conductive agent and the second active material. The mass of the second active material is obtained by weighing. Under air / oxygen conditions, a thermogravimetric analyzer (such as TGA) is used to analyze the second active material. The intermediate powder used in the test is 5~15mg. Under an air or oxygen atmosphere, the temperature is increased from room temperature to 900℃ at a rate of 10℃ / min and held at 900℃ for 40min. This allows the non-silicon components in the intermediate powder to volatilize while the silicon is fully oxidized to silicon dioxide. The weight percentage of the test process is the ash content of the second active material. The ash content is divided by the molar mass of silicon dioxide (60) and then multiplied by the molar mass of silicon (28) to obtain the percentage of silicon in the second active material. Based on the silicon content in the second active material, the silicon-carbon material content B in the second active material can be calculated. According to SEM-EDS, the mass percentage of silicon element A in the spherical silicon-carbon material can be obtained. The content of the second graphite is obtained by subtracting the content of silicon-carbon material from the total content of silicon-carbon material and second graphite (compared to the content of graphite, the content of conductive agent is small and can usually be ignored. Therefore, the total mass percentage of graphite and conductive agent in the second negative electrode active layer can be equated to the mass percentage of graphite in the second negative electrode active layer).

[0097] In one possible implementation, the silicon-carbon material comprises a porous carbon framework and silicon particles located in the pores of the porous carbon framework.

[0098] When silicon-carbon materials employ a porous carbon framework and silicon particles embedded within it, the porous carbon framework provides ample internal void space, effectively accommodating the volume expansion of silicon particles during lithium insertion / extraction, significantly mitigating the volume effect of silicon, and preventing electrode structure cracking, pulverization, and active material shedding. Simultaneously, the continuous porous carbon framework can construct a stable and efficient conductive network, improving the poor conductivity of silicon particles themselves, enhancing electron transport efficiency and ion transport channels, and promoting rapid lithium-ion diffusion. Furthermore, this structure reduces direct contact between silicon particles and the electrolyte, suppressing side reactions and the repeated formation of unstable SEI films, and reducing interfacial impedance growth. Thus, while fully leveraging the high specific capacity advantage of silicon materials and increasing battery energy density, it significantly improves the battery's cycle stability and rate charge / discharge performance.

[0099] Building upon the foregoing embodiments, the first solid electrolyte further comprises at least one of Al, Ti, and La. The first solid electrolyte can form a stable ion-conducting phase using at least one of oxides or phosphates containing aluminum, titanium, or lanthanum. This type of material can both construct a mechanically constrained layer on the surface of spherical silicon-carbon materials and maintain structural integrity during silicon lithium intercalation expansion, thereby suppressing particle pulverization and repeated interfacial cracking. In some embodiments, La can induce the formation of an inorganic SEI film comprising La-F bonds and / or La-O bonds on the surface of the silicon-carbon material, significantly suppressing electrolyte decomposition and interfacial cracking caused by the volume expansion of the silicon-carbon material.

[0100] Furthermore, the first solid electrolyte includes at least one of lithium aluminum titanium phosphate, lithium lanthanum titanate, and lithium lanthanum zirconium oxide. These materials possess good high voltage stability, high lithium-ion mobility, and interfacial compatibility with the silicon system. Their reaction mechanism involves transferring lithium ions through a stable framework and providing buffering support for changes in silicon particle volume. Further, lithium aluminum titanium phosphate may contain La doping, for example, Li... 1.3 Al 0.2 La 0.1 Ti 1.7 (PO4)3. In this application, when the first solid electrolyte includes lithium aluminum titanium phosphate, the second negative electrode active layer includes Al; when the first solid electrolyte includes lithium aluminum titanium phosphate and / or lithium lanthanum titanate, the second negative electrode active layer includes Ti; when the first solid electrolyte includes at least one of lithium lanthanum titanate, lithium lanthanum zirconium oxide, and La-doped lithium aluminum titanium phosphate, the second negative electrode active layer includes La.

[0101] In one possible implementation, the first solid electrolyte comprises 0.1%-5% by mass in the second negative electrode active layer. This range allows the first solid electrolyte to cover the surface of the spherical silicon-carbon material and fill the gaps between the particles with a low addition amount, avoiding dilution of the electron pathway due to excessive dosage, while still forming a continuous ion transport and mechanical confinement network. By controlling this ratio within the preferred range, interface stability can be enhanced while maintaining a high capacity contribution, thereby reducing the risk of electrode expansion and internal short circuits.

[0102] For example, in the second negative electrode active layer, the mass percentage of the first solid electrolyte can be any one of 0.1%, 0.5%, 1%, 2.05%, 3.1%, 4.6%, 4.8%, 5%, or any combination thereof.

[0103] In some implementations, SEM-EDS can be used to test the negative electrode and determine the mass ratio of spherical silicon-carbon material to the first solid electrolyte in the second negative electrode active layer based on the silicon content and the metal content in the solid electrolyte.

[0104] Furthermore, in the second negative electrode active layer, when the first solid electrolyte includes lithium aluminum titanium phosphate, the mass ratio of aluminum to silicon is controlled at 0.03% to 0.15%; and / or, when the first solid electrolyte includes lithium aluminum titanium phosphate and / or lithium lanthanum titanate, the mass ratio of titanium to silicon is controlled at 0.4% to 2.1%; and / or, when the first solid electrolyte includes at least one of lithium lanthanum titanate, lithium lanthanum zirconium oxide, and La-doped lithium aluminum titanium phosphate, the mass ratio of lanthanum to silicon is controlled at 0.05% to 0.4%. Aluminum is used to optimize the framework stability of the first solid electrolyte and improve the density of the interfacial film; titanium helps to improve the stability of the crystal structure and the continuity of lithium-ion migration channels; and lanthanum enhances the mechanical strength and stress resistance of the material. These proportions ensure effective constraint of silicon expansion by the first solid electrolyte without reducing the content of active materials or hindering the formation of the conductive network due to excessive inorganic phase. This process achieves stress dispersion and interface stabilization during lithium insertion and / or delithiation of silicon-carbon materials, thereby ensuring that the negative electrode still has lower electrode thickness growth, a more stable SEI film, and better cycle life under high rate, high temperature, and long cycle conditions.

[0105] For example, in the second negative electrode active layer, the mass ratio of aluminum to silicon can be any one of 0.03%, 0.05%, 0.06%, 0.08%, 0.15%, or any combination thereof.

[0106] In the second negative electrode active layer, the mass ratio of titanium to silicon can be any one of 0.4%, 1.3%, 1.5%, 2%, 2.1%, or any combination thereof.

[0107] In the second negative electrode active layer, the mass ratio of lanthanum to silicon can be any one of 0.05%, 0.08%, 0.10%, 0.11%, 0.35%, or any combination thereof.

[0108] In some implementations, the second negative electrode active layer can be scraped off, and the content of each element in the second negative electrode active layer can be tested using ICP.

[0109] Building upon the foregoing embodiments, the spherical silicon-carbon material further comprises a silicon-carbon matrix and a carbon layer located on at least a portion of the surface of the silicon-carbon matrix. The spherical silicon-carbon material employs a core-shell or semi-encapsulated structure with a carbon layer encapsulated on the silicon-carbon matrix. The carbon layer is preferably formed of amorphous carbon, graphitized carbon, pitch carbon, or resin carbon to improve conductivity and buffer silicon expansion. Furthermore, when the ratio of the Dv50 of the first solid electrolyte to the thickness of the carbon layer is controlled to be 1-3, the particle size of the first solid electrolyte can be matched with the scale of the encapsulation layer, enabling it to stably adhere to the surface of the carbon layer without disrupting the continuity of the carbon layer, thereby constructing a uniform ion channel.

[0110] For example, the ratio of the Dv50 of the first solid electrolyte to the thickness of the carbon layer can be any of 1, 2, 2.5, 3 or any combination thereof.

[0111] In one possible implementation, at least a portion of the surface of the spherical silicon-carbon material is coated with a first solid electrolyte. The ratio of the Dv50 of the spherical silicon-carbon material to the Dv50 of the first solid electrolyte is 20 to 200, indicating that the particle size of the spherical silicon-carbon material is significantly larger than that of the first solid electrolyte particles. This allows the fine first solid electrolyte to be more fully distributed on at least a portion of the surface of the large silicon-carbon material particles and form an interface modification, thereby improving ion transport and interface stability.

[0112] For example, the ratio of Dv50 of the spherical silicon-carbon material to Dv50 of the first solid electrolyte is a range of any one or any two of 20, 30, 40, 50, 70, 100, 107, and 200. Further, the ratio of Dv50 of the spherical silicon-carbon material to Dv50 of the first solid electrolyte is 20 to 107.

[0113] Furthermore, when the Dv50 of the spherical silicon-carbon material is 1μm~20μm; and / or the Dv50 of the first solid electrolyte is 10nm~1000nm, the fine first solid electrolyte particles can uniformly fill the gaps between the spherical silicon-carbon material particles. This not only constructs a continuous and interconnected lithium-ion transport pathway inside the second negative electrode active layer, significantly reducing interface impedance and improving battery rate performance, but also buffers the huge volume expansion of the silicon-carbon material during charging and discharging with the help of the first solid electrolyte particles, alleviating particle pulverization and conductive network breakage problems. At the same time, it increases the compaction density and overall energy density of the negative electrode sheet, reduces the voids inside the first negative electrode active layer, suppresses interface degradation during cycling, and effectively improves the cycle stability and long cycle life of the solid-state battery.

[0114] For example, the Dv50 of the spherical silicon carbide material is a range of any one or any two of 1 μm, 3 μm, 7 μm, 10 μm, 15 μm, 20 μm;

[0115] The Dv50 of the first solid electrolyte is a range of any one or any two of 10nm, 80nm, 100nm, 500nm, and 1000nm.

[0116] In one possible implementation, the porosity ratio of the first negative electrode active layer to the second negative electrode active layer is 1-1.9. By increasing the porosity of the bottom layer, liquid phase transport is accelerated, allowing lithium from the positive electrode to diffuse to the bottom layer more quickly. Simultaneously, the extra porosity provides expansion space, addressing the issues of large expansion during full charge and cycling. A reasonable porosity ratio can effectively alleviate the problem of uneven stress distribution between the first and second negative electrode active layers during charging and discharging, buffering the volume expansion of the second negative electrode active layer, preventing deformation, cracking, or peeling of the negative electrode sheet, while reducing the risk of interface polarization and lithium plating. This balances battery energy density, cycle stability, and fast-charging performance, improving overall structural reliability and electrochemical consistency.

[0117] For example, the ratio of the porosity of the first negative electrode active layer to the porosity of the second negative electrode active layer can be any one of 1, 1.1, 1.34, 1.5, 1.7, 1.9, or any combination thereof. Further, the ratio of the porosity of the first negative electrode active layer to the porosity of the second negative electrode active layer is 1.1-1.3.

[0118] In one embodiment, when the porosity of the first negative electrode active layer is 10-60%, the conductive contact between the first negative electrode active layer and the negative electrode current collector can be improved, as well as the compaction capacity of the first negative electrode active layer can be improved.

[0119] In some implementations, when the porosity of the second negative electrode active layer is 15-50%, a buffer space for the lithium insertion / extraction expansion of silicon-carbon materials can be reserved.

[0120] In some implementations, by differentiating the porosity of the first and second negative electrode active layers, it is possible to ensure smooth electron conduction between the first and second negative electrode active layers and the negative electrode current collector, thereby reducing the overall internal resistance of the negative electrode sheet. At the same time, the sufficient porosity of the second negative electrode active layer can buffer the huge volume deformation of the silicon-carbon material, preventing the second negative electrode active layer from bulging and cracking and the failure of the conductive network. Furthermore, the layered control of porosity can balance the lithium-ion transport resistance of the two layers, weaken the concentration polarization inside the negative electrode sheet, and significantly improve the rate performance and long-cycle stability of the negative electrode sheet.

[0121] For example, the porosity of the first negative electrode active layer is a range of any one of 10%, 20%, 40%, 50%, 60%, or any two of them.

[0122] The porosity of the second negative electrode active layer is within the range of any one of 15%, 20%, 40%, and 50%, or any combination thereof.

[0123] In some implementations, the porosity of the first negative electrode active layer and the second negative electrode active layer can be obtained based on the FIB of the negative electrode sheet.

[0124] Furthermore, the first negative electrode active layer includes a lithium replenishing agent, which can compensate for initial lithium loss during film formation or formation and participate in interface repair, thereby improving initial efficiency and stability. For example, the lithium replenishing agent includes lithium powder.

[0125] In one possible implementation, the first negative electrode active layer includes a first additive, and the second negative electrode active layer includes a second additive; the first and / or second additive includes at least one of a binder, a conductive agent, and a dispersant; the mass percentage of the second additive in the second negative electrode active layer to the mass percentage of the first additive in the first negative electrode active layer is 1.5-5. By giving the second negative electrode active layer a higher bonding and constraint capacity, particle shedding and interlayer cracking caused by silicon expansion can be more effectively suppressed, while maintaining a relatively low or moderate additive content in the first negative electrode active layer is beneficial for conductive network formation and increased compaction density. In some embodiments, the first additive includes a conductive agent, a binder, and a dispersant; the second additive includes a conductive agent, a binder, and a dispersant. The materials of the first and second additives can be the same or different.

[0126] For example, the ratio of the mass percentage of the second auxiliary agent in the second negative electrode active layer to the mass percentage of the first auxiliary agent in the first negative electrode active layer can be any one of 1.5, 2, 3, 4, 5 or any combination thereof.

[0127] In one possible implementation, the surface of the second negative electrode active layer away from the negative electrode current collector 11 has N first recesses, where N ≥ 1. These N first recesses are formed on the surface of the second negative electrode active layer away from the negative electrode current collector 11 through embossing, laser etching, local molding, or roll forming, transforming the surface from a flat structure into a microstructured surface with localized accommodating spaces. This serves to allow the first recesses to act as stress relief zones and expansion buffers when the silicon-carbon material undergoes volume expansion during lithium insertion and extraction, mitigating surface bulging, crack propagation, and interface delamination. In some embodiments, the first recesses can be grooves.

[0128] In one possible implementation, the distance between two adjacent first recesses is preferably 0.1 μm-5 μm. By controlling the distribution density of the first recesses, a balance is maintained between the local buffer space and the surface continuity. If the spacing is too small, it will cause excessive local weakening of the negative electrode active layer, affecting the areal capacity and mechanical integrity; if the spacing is too large, it will be difficult to release stress in a timely manner. Limiting the spacing within the above range allows multiple recesses to work together to form a continuous stress adjustment channel, while also taking into account the uniformity of electrolyte wetting and lithium-ion transport.

[0129] The depth of the first recess is preferably 0.1 μm-25 μm, which determines the volume provided by the recess and its capacity to accommodate expansion. Shallower recesses are suitable for slight control of surface morphology, while deeper recesses can provide stronger local buffering capacity without excessively disrupting the structural continuity of the second negative electrode active layer. By controlling the depth within this range, the risk of particle extrusion, adhesion failure, and localized short circuits can be reduced while suppressing the expansion of the fully charged thickness.

[0130] The first recess, preferably 20 μm-200 μm in length of the negative electrode, allows for the formation of fine and effective microgrooves or pits in the coating direction. The reaction mechanism lies in the fact that this structure guides the electrolyte to more uniformly wet the active layer and provides an orderly release path for the volume changes of the silicon-carbon material, thereby reducing local concentration polarization and stress concentration. Consequently, the second negative electrode active layer maintains more stable structural integrity during charge-discharge cycles, thus improving cycle life, rate performance, and safety.

[0131] For example, the distance between two adjacent first recesses is a range of any one of 0.1μm, 0.5μm, 1μm, 3μm, 5μm, or any two of them;

[0132] The depth of the first recess can be any one of 0.1μm, 0.5μm, 1μm, 4μm, 10μm, 25μm or a range of any two of them;

[0133] The dimension of the first recess along the length of the negative electrode sheet can be any one of 20μm, 30μm, 100μm, 150μm, 200μm, or any combination thereof.

[0134] In some implementations, the presence or absence of a first recess in the negative electrode sheet, as well as the size and distribution of the first recess, can be determined based on the surface SEM image and cross-sectional SEM image of the negative electrode sheet.

[0135] A second aspect of this application also provides a battery, which includes the negative electrode sheet of the first aspect.

[0136] In this embodiment, by arranging the high-silicon component on the surface layer and the graphite support layer on the bottom layer, and combining spherical silicon particles, first solid electrolyte interface modification and graphite Raman parameter matching, it is possible to effectively suppress cycle expansion and interface damage while ensuring a high specific capacity, improve the uniformity of lithium ion transport in the thickness direction, and thus improve the cycle stability, full-charge dimensional stability and safety of the battery.

[0137] Building upon the aforementioned embodiments, the system further includes a positive electrode sheet, comprising a positive current collector and a positive active layer located on at least one side of the positive current collector surface. The positive active layer includes a second solid electrolyte. The second solid electrolyte can serve as an ion transport phase dispersed in the positive active layer, or exist in the coating in a particle-loaded, locally enriched manner, thereby constructing a more stable lithium-ion channel within the positive electrode and reducing interfacial side reactions. Since the second solid electrolyte combines ion conduction and interfacial passivation, its addition can reduce repeated film rupture caused by direct contact between the positive electrode particles and the electrolyte, thereby suppressing polarization rise and capacity decay.

[0138] This application does not specifically limit the second solid electrolyte, which can be any solid electrolyte commonly used in the art. For example, the second solid electrolyte can be at least one of garnet-type solid electrolyte, perovskite-type solid electrolyte, and sulfide solid electrolyte. Further, the second solid electrolyte includes at least one of lithium aluminum titanium phosphate, lithium lanthanum titanate, and lithium lanthanum zirconium oxide. In this application, the first solid electrolyte and the second solid electrolyte can be the same or different.

[0139] In one possible implementation, the mass percentage of the second solid electrolyte in the positive electrode active layer is 0.01%-0.1%, which can achieve interface stabilization without significantly diluting the positive electrode active material. If the content is too low, the ion channels and protective effect are insufficient; if the content is too high, it may increase the internal resistance of the positive electrode active layer and affect the compaction density. Therefore, this range can achieve a balance between energy density, rate performance, and cycle stability. The reaction mechanism lies in the fact that a small amount of the second solid electrolyte forms continuous or semi-continuous ion migration pathways within the positive electrode active layer and acts as a buffer and isolation agent at the electrode / electrolyte interface, thereby improving structural stability under high temperature and long-cycle conditions.

[0140] For example, the mass percentage of the second solid electrolyte can be any one of 0.01%, 0.02%, 0.03%, 0.07%, 0.1%, or a range of any two thereof.

[0141] In some implementations, ICP can be used to test the positive electrode active layer to obtain the content of each metal element in the positive electrode active layer, thereby confirming the content of the second solid electrolyte in the positive electrode active layer.

[0142] In one possible implementation, the ratio of the Dv50 of the spherical silicon-carbon material to the Dv50 of the second solid electrolyte is 20-200, which allows the particle size of the silicon-carbon particles on the negative electrode side to match the particle size of the second solid electrolyte on the positive electrode side. Dv50 represents the particle size corresponding to a cumulative volume fraction of 50% in the particle size distribution, typically expressed in μm or nm; this ratio reflects the relative coordination between the two types of particles in terms of scale. This particle size matching improves the uniformity of the internal pore distribution and interfacial contact of the electrode, reduces local ion concentration differences and stress concentration, thereby lowering the risk of lithium plating, swelling, and internal short circuits during charging and discharging.

[0143] Therefore, matching a small amount of second solid electrolyte in the positive electrode with spherical silicon-carbon material of a specific particle size can improve the interface transport efficiency and thermal stability while ensuring the high utilization rate of the positive electrode. Combined with the structural design of the silicon-containing negative electrode, the battery can balance capacity output, cycle life and safety under high energy density conditions, thereby achieving more stable overall battery performance.

[0144] For example, the ratio of Dv50 of the spherical silicon-carbon material to Dv50 of the second solid electrolyte can be any of 20, 25, 30, 40, 100, 107, 200, or any combination thereof. Further, the ratio of Dv50 of the spherical silicon-carbon material to Dv50 of the second solid electrolyte is 20 to 107.

[0145] In one possible implementation, when the Dv50 of the second solid electrolyte is 10nm~1000nm, the second solid electrolyte particles can uniformly fill the gaps between the positive electrode active material particles, constructing a continuous and stable lithium-ion conduction channel, reducing contact resistance, improving rate charge and discharge performance, and avoiding the increase in voids and decrease in compaction density of the positive electrode active layer caused by excessively large second solid electrolyte particles. It can also prevent the agglomeration of second solid electrolyte particles that block the ion pathway due to excessively fine particle size. Furthermore, it can alleviate interfacial side reactions under high-voltage charge and discharge, reduce polarization and capacity decay, and effectively improve the energy density and cycle life of the battery.

[0146] For example, the Dv50 of the second solid electrolyte is a range of any one or any two of 10 nm, 80 nm, 100 nm, 500 nm, and 1000 nm.

[0147] In some implementations, HRTEM can be used to confirm the Dv50 of the second solid electrolyte in the positive electrode.

[0148] Building upon the aforementioned embodiments, the positive electrode active layer further includes a positive electrode active material, comprising lithium cobalt oxide, which incorporates doping elements, including Y and / or La. In other words, in addition to the second solid electrolyte, the positive electrode active layer introduces a positive electrode active material primarily composed of lithium cobalt oxide, enabling the positive electrode layer to possess both high lithium intercalation capacity and interface stability. As a layered oxide positive electrode material, lithium cobalt oxide, through Y and / or La doping in its lattice, can utilize the strong structural support of rare earth elements to reduce lattice collapse and phase transition tendencies under high-voltage charging / discharging and thermal stress. The reaction mechanism lies in the fact that after Y and / or La enter the lithium cobalt oxide lattice, they regulate the local coordination environment and bond energy distribution, thereby slowing cobalt migration, suppressing side reactions, and improving particle surface stability and electrolyte compatibility.

[0149] In some embodiments of this application, when the mass percentage of element M in lithium cobalt oxide is 0.005%-0.6%, effective passivation and structural reinforcement of the lithium cobalt oxide lattice can be achieved at a low doping level, while avoiding lattice distortion, reduction of active sites and obstruction of ion diffusion caused by excessive doping, thereby improving the cycle performance and capacity of the battery.

[0150] For example, in lithium cobalt oxide, the mass percentage content of element M can be any one of 0.005%, 0.009%, 0.01%, 0.02%, 0.3%, 0.4%, 0.6%, or any combination thereof.

[0151] Furthermore, when the mass percentage of Y in lithium cobalt oxide is 0.005%-0.3%, effective passivation and structural reinforcement of the crystal lattice can be achieved at a low doping level, while avoiding lattice distortion, reduction of active sites, and hindered ion diffusion caused by excessive doping. Similarly, when the mass percentage of La in lithium cobalt oxide is 0.005%-0.3%, high-temperature cycling stability and rate response can be enhanced while maintaining the bulk capacity of the material. This range is set based on the need for a balance between material stabilization and electrochemical activity. By limiting the total amount of rare earth doping within a narrow range, the doping is sufficient to improve the integrity of the layered structure without significantly increasing polarization or reducing reversible capacity.

[0152] When Y and La act synergistically as doping elements in lithium cobalt oxide, they can improve the mechanical integrity of the positive electrode active layer during compaction, winding, and long-term cycling. Simultaneously, they can slow down the interface degradation between the positive electrode surface and the second solid electrolyte, reducing the rate of impedance growth. This process achieves stable internal structure of the positive electrode particles, a more uniform interface film, and smoother repeated lithium insertion / extraction processes. This improves the battery's capacity retention, cycle life, and safety under high-rate, high-temperature, and long-cycle conditions. Furthermore, it synergizes with the structural design of the negative electrode side, further enhancing the overall performance of the battery.

[0153] For example, in lithium cobalt oxide, the mass percentage content of element Y can be any one of 0.005%, 0.009%, 0.01%, 0.02%, 0.3%, or a range of any two thereof;

[0154] The mass percentage of La can be any one of 0.005%, 0.009%, 0.01%, 0.02%, 0.3%, or any combination thereof.

[0155] In some implementations, the positive electrode active layer can be subjected to SEM-EDS testing to obtain the content of La and Y in lithium cobalt oxide.

[0156] Figure 3 This is a schematic diagram of the positive electrode sheet from one perspective in some embodiments of this application; Figure 4 This is a schematic diagram of the positive electrode structure from another perspective in some embodiments of this application. For example... Figure 3 as well as Figure 4 As shown, in one possible implementation, the surface of the positive electrode active layer away from the positive electrode current collector has Q second recesses 221, where Q ≥ 1. The second recesses 221 can be formed by drilling, wire bonding, surface scanning, etc., and can further improve the electrolyte wettability of the positive electrode active layer, thereby enhancing the battery's ion transport capability. For example, the cross-section of the second recess 221 can be circular.

[0157] Furthermore, when the distance between the center points of two adjacent second recesses 221 is 100μm-2000μm, the coverage of the second recesses is more uniform and stress superposition caused by local over-density can be avoided; the width of the second recess 221 is 6μm-150μm (when the cross-section of the second recess 221 is circular, the width refers to the diameter of the circle) which is beneficial for stable forming under limited processing precision and improves the efficiency of electrolyte entry and lithium-ion transport; the depth of the second recess 221 is 3μm-25μm (the maximum depth of the second recess 221), which can further precisely control the penetration depth of the electrolyte into the electrode and Uniform wetting ensures rapid and smooth lithium-ion transport during charging and discharging, reducing concentration polarization and interface impedance. Simultaneously, it prevents the second recess 221 from being too deep, which could damage the positive electrode current collector and lead to structural damage or short circuits. It also prevents the second recess 221 from being too shallow, which would fail to effectively improve mass transfer within the positive electrode. Combined with the gradient structure design of the negative electrode, this further enhances the battery's fast-charging performance and rate response. Furthermore, an appropriate depth optimizes the stress distribution within the positive electrode, mitigating volume deformation during charging and discharging, improving the structural stability and cycle life of the positive electrode, and balancing the battery's energy density, safety, and long-term reliability.

[0158] Based on the aforementioned embodiments, the surface of the positive electrode active layer away from the positive electrode current collector has L third recesses. The third recesses are formed on the side of the positive electrode active layer away from the positive electrode current collector by embossing, molding or rolling. The third recesses can be local depressions or arrayed distributions, which are used to increase the effective surface area and improve electrolyte wetting without significantly weakening the overall strength of the electrode.

[0159] Furthermore, the depth of the third recess is >60μm, which can form sufficient ion channels while avoiding material damage, powder shedding or uneven compaction caused by excessively deep structures. This is because this depth range takes into account both shortening the surface diffusion path and maintaining the mechanical integrity of the electrode.

[0160] For example, the depth of the third recess can be any one of 61μm, 70μm, 80μm, 90μm, 100μm or any combination thereof;

[0161] The distance between the center points of two adjacent second recesses 221 can be any one of 100μm, 120μm, 140μm, 200μm, 1000μm, 2000μm or any combination thereof;

[0162] The width of the second recess 221 can be any one of 6μm, 7μm, 8μm, 9μm, 10μm, 80μm, 100μm, 150μm or any combination thereof;

[0163] The depth of the second recess 221 can be any one of 3μm, 13μm, 15μm, 20μm, 22μm, 23μm, 25μm or any combination thereof.

[0164] In some embodiments, when the distance between the end of the second recess 221 and the edge of the positive electrode is 0.5mm-1mm in the width direction of the positive electrode, the service life of the positive electrode can be extended.

[0165] Furthermore, when the battery adopts a wound structure, the positive electrode sheet includes alternating straight sections and bent sections along the winding direction, and the positive electrode active layer of the bent section has Q' second recesses, where Q'≥1.

[0166] By incorporating Q' second recesses in the bending section of the positive electrode sheet, compensation can be provided for areas most prone to stretching and stress concentration during winding. This results in a more consistent deformation response between the bending and straight sections, thereby reducing the risk of electrode wrinkling, positive electrode active layer cracking, and localized delamination. Furthermore, the surface microstructure formed by the second recesses enhances the wettability of the positive electrode surface and provides a more continuous ion exchange interface, thereby reducing local polarization and improving charge-discharge consistency. This leads to more stable capacity output and superior structural safety of the battery during high-rate operation and cycling.

[0167] In this application, the third recess and the second recess 221 may at least partially overlap, or they may not overlap. In some embodiments, it can be determined whether the positive electrode sheet includes the third recess and the second recess, and the depth of the second recess, the size of the third recess, and the distribution can be confirmed based on the surface SEM image and the cross-sectional SEM image of the positive electrode sheet.

[0168] Building upon the aforementioned embodiments, the system further includes an electrolyte comprising fluoroethylene carbonate. As a fluorocarbonate component with excellent film-forming activity, fluoroethylene carbonate preferentially participates in the negative electrode interface reaction during the first charge. Its reaction mechanism lies in the fact that the fluorine-containing groups in the molecule lower the reduction decomposition threshold and promote the formation of a dense SEI film rich in inorganic components such as LiF, thereby inhibiting continuous electrolyte decomposition, reducing heat generation from side reactions, and slowing down lithium deposition. For silicon-doped graphite negative electrodes, this type of electrolyte helps compensate for the repeated rupture of the interface film caused by volume changes in silicon materials, thereby improving interface stability and cycle life.

[0169] Preferably, the mass percentage of fluoroethylene carbonate in the electrolyte is 5-18%. Controlling this within this range ensures the effective amount required for forming a stable interfacial film while avoiding excessive addition that could lead to increased electrolyte viscosity, impaired ion transport, or decreased low-temperature performance. Typically, around 8% is sufficient for basic film formation, while concentrations closer to 18% enhance film integrity under high-temperature and long-cycle conditions. Adjusting the concentration between 5-18% allows for optimization of the interfacial reaction rate and film density based on the anode silicon content, rate capability, and service temperature. This content window allows the electrolyte to work synergistically with the morphology control of the layered anode structure and spherical silicon-carbon materials, enabling faster establishment of a stable interface and reducing persistent side reactions during charge and discharge. This reduces polarization, suppresses lithium plating and internal short-circuit risks, and further improves battery capacity retention, cycle stability, and safety.

[0170] For example, the mass percentage of fluoroethylene carbonate in the electrolyte is any one of 5%, 8%, 9%, 10%, 15%, and 18%, or any combination thereof. Further, the mass percentage of the fluoroethylene carbonate in the electrolyte is 8-18%.

[0171] In some implementations, GC-MS can be used to test the content of fluoroethylene carbonate in the electrolyte.

[0172] This application also provides an electronic device including the aforementioned battery. This battery exhibits excellent energy density and cycle performance under high voltage, making it suitable for various electronic devices (e.g., new energy vehicles and energy storage devices).

[0173] The present invention will be further described below with reference to specific embodiments.

[0174] Unless otherwise specified, the experimental methods described in the following examples are conventional methods; and the reagents and materials are commercially available unless otherwise specified.

[0175] Example 1

[0176] The battery in this embodiment is prepared by a method including the following steps:

[0177] 1) Preparation of negative electrode sheet

[0178] The second negative electrode active layer slurry comprises, by weight percentage: 90% second active material, 3% Li 1.3 Al 0.2 La 0.1 Ti 1.7 The composition includes (PO4)3 (first solid electrolyte), 4.2% PVDF, 2.5% CMC, and 0.3% carbon black; the second active material includes 43% silicon-carbon material (including a silicon-carbon matrix and a carbon layer located on at least a portion of the surface of the silicon-carbon matrix, the silicon-carbon matrix including a porous carbon skeleton and silicon particles located in the pores of the porous carbon skeleton) and 57% second graphite; the first solid electrolyte is coated on at least a portion of the surface of the silicon-carbon material; the ratio of the Dv50 of the first solid electrolyte to the thickness of the carbon layer is 2.5; the ratio of the Dv50 of the spherical silicon-carbon material to the Dv50 of the first solid electrolyte is 70.

[0179] The first negative electrode active layer slurry comprises, by weight percentage: 94.9% first graphite, 1% PVDF, 0.3% CMC, 1.5% carbon black, and 2.3% lithium powder.

[0180] The first and second negative electrode active layer slurries were uniformly coated on both surfaces of a 5μm copper foil at a 7:3 areal density ratio. After drying, the foil was rolled and cut into 73mm pieces. A small 1458mm wafer is used to obtain a negative electrode sheet including a first negative electrode active layer and a second negative electrode active layer. Then, laser wire bonding is performed to form a first recess. The laser wire bonding can penetrate the second negative electrode active layer. The size of the first recess in the extension direction of the negative electrode sheet is 73μm, the distance between two adjacent first recesses is 1.2μm, and the average depth of the first recess is 8μm.

[0181] In the Raman spectrum, the first graphite is at a wavelength of 1530 cm⁻¹. -1 ~1590cm -1 Peak intensity I G With a wavelength of 1330cm -1 ~1390cm -1 Peak intensity ID The second graphite at a wavelength of 1530 cm -1 ~1590cm -1 The peak intensity IG' is at a wavelength of 1330 cm⁻¹ -1 ~1390cm -1 Peak intensity I D 'Satisfy: I D / I G It is 0.69, I D ' / I G 'It is 0.451;

[0182] Obtain a cross-sectional SEM image of the negative electrode, such as... Figure 1 as well as Figure 2 As shown, all angles in the cross-section of the spherical silicon-carbon material are >120°, and the cross-section is located on the surface of the second negative electrode active layer away from the negative electrode current collector.

[0183] Figure 5 This is the Raman spectrum of the negative electrode in Embodiment 1 of this application; Figure 6 This is a Raman spectral density diagram of the graphite in the negative electrode sheet of Embodiment 1 of this application. Since silicon-carbon materials also contain carbon, therefore... Figure 5 The ID / IG ratio of the negative electrode is very large, so values ​​greater than 1 need to be filtered out. Figure 6 For based on Figure 5 After filtering out data with ID / IG greater than 1, it can be seen that in the negative electrode sheet of Example 1, the ID / IG of the second negative electrode active layer is less than the ID / IG of the first negative electrode active layer, that is, the ID' / IG' of the second graphite is less than the ID / IG of the second graphite.

[0184] 2) Preparation of positive electrode sheet

[0185] The mixture consists of LiCoO2 (doped with Y and La): conductive carbon black: PVDF: Li 1.3 Al 0.2 La 0.1 Ti 1.7 (PO4)3 (second solid electrolyte) was mixed in a mass ratio of 9.5:0.1:0.1:0.3, and then stirred in a planetary mixer for 12 hours to obtain a positive electrode active layer slurry. The positive electrode active layer slurry was uniformly coated on both surfaces of an 8 μm thick aluminum foil, dried in an oven at 60°C for 24 hours, and then cut into 71 mm pieces. The positive electrode sheet with a size of 1456mm, including the positive electrode active layer, needs to be cut into a circular arc to form a second concave part, and then embossed to form a third concave part.

[0186] The second concave portion has a circular cross-section with a diameter of 8±2μm; the distance between the center points of two adjacent second concave portions is 150μm±50μm; the maximum depth of the third concave portion is 23μm; and the average depth of the third concave portion is 80μm.

[0187] 3) Electrolyte preparation

[0188] 1 M LiPF6 was dissolved in a 1:1 EC and DMC solution to obtain a reference electrolyte. Then, 15% FEC was added to obtain the final electrolyte (the FEC content in the electrolyte was 13%).

[0189] 4) Preparation of lithium-ion batteries

[0190] After assembling the positive electrode, separator, and negative electrode into an electrode assembly by winding, the electrode assembly is stacked and pressed for 100 seconds at approximately 90°C and 250 kgf using hot pressing. Subsequently, the electrode assembly is housed in a casing, electrolyte is injected into it, and then vacuum sealed to obtain a lithium-ion battery; the specific parameters of the battery are shown in Tables 1 and 2.

[0191] The preparation methods of the batteries in Examples 2-21 and Comparative Examples 1-4 are basically the same as those in Example 1, with the differences shown in Table 1 and Table 2.

[0192] In Example 2, the second active material in the second negative electrode active layer slurry has a mass percentage content of 92%; the second active material includes 20% silicon-carbon material and 80% second graphite.

[0193] In Example 3, the second active material in the second negative electrode active layer slurry has a mass percentage content of 88%; the second active material includes 66.66% silicon-carbon material and 33.34% second graphite.

[0194] In Example 9, the mass percentage of the first negative electrode active layer slurry includes: 95.08% first graphite, 1% PVDF, 0.3% CMC, 1.5% carbon black, and 2.12% lithium powder;

[0195] In Example 10, the mass percentage of the first negative electrode active layer slurry includes: 94.67% first graphite, 1% PVDF, 0.3% CMC, 1.5% carbon black, and 2.53% lithium powder;

[0196] In Example 21, the negative electrode is not scribed, the positive electrode is not perforated, and the lithium cobalt oxide does not contain Y or La;

[0197] In Comparative Example 1, the second negative electrode active layer slurry was directly coated on both sides of the copper foil.

[0198] In Comparative Example 3, the second negative electrode active layer slurry does not include the first solid electrolyte.

[0199] Performance testing

[0200] The following performance tests were performed on the batteries of the examples and comparative examples, and the results are shown in Table 2.

[0201] 1) 25℃ Cyclic Test

[0202] Under ambient temperature of 25℃, the battery was charged at a constant current rate of 1C to 4.55V, then charged at a constant voltage of 4.55V until the current equals 0.02mA. It was then discharged at a discharge rate of 1C to 2.8V, and this charge-discharge cycle was repeated 400 times. The discharge capacity Q1 of the battery during the first cycle and the discharge capacity Q400 of the battery during the 400th cycle were measured. The capacity retention rate after 400 cycles is calculated as Q = Q400 / Q1 × 100%.

[0203] 2) 45℃ Cyclic Test

[0204] Under ambient temperature of 45℃, the battery was charged at a constant current rate of 1C to 4.55V, then charged at a constant voltage of 4.55V until the current equals 0.02mA. It was then discharged at a discharge rate of 1C to 2.8V, and this charge-discharge cycle was repeated 400 times. The discharge capacity Q1' of the battery during the first cycle and Q400' of the battery during the 400th cycle were measured. The capacity retention rate after 400 cycles is calculated as Q' = Q400' / Q1' × 100%.

[0205] 3) Room temperature full charge expansion rate test

[0206] At an ambient temperature of 25℃, the battery was fully charged and then discharged to 60% SOC. Under a force of 600g, the initial thickness of the battery at 60% SOC was tested. Referring to the charge and discharge regime in 1), the thickness of the battery after the first charge and discharge and after 400T cycles were tested. The room temperature full charge expansion rate = battery thickness after the first discharge / initial thickness at 60% SOC - 1; the cycle full charge expansion rate = battery thickness after cycle / initial thickness at 60% SOC - 1.

[0207] 4) High-temperature full-charge expansion rate test

[0208] At an ambient temperature of 45℃, the battery was fully charged and then discharged to 60% SOC. Under a force of 600g, the initial thickness of the battery at 60% SOC was tested. Referring to the charge and discharge regime in 1), the thickness of the battery after the first charge and discharge and after 400T cycles were tested. The room temperature full charge expansion rate = battery thickness after the first discharge / initial thickness at 60% SOC - 1; the cycle full charge expansion rate = battery thickness after cycle / initial thickness at 60% SOC - 1.

[0209] 5) K-value test

[0210] Charge the battery to 3.926~4.000V at 0.5C, let it stand at 45℃ for 48 hours, and after the battery cools down, measure voltage 1. Then let it stand at room temperature for 48 hours and measure voltage 2. K value = (voltage 1 - voltage 2) / room temperature standing time (h). Test 10 batteries for each parameter and take the average value.

[0211] Table 1

[0212]

[0213]

[0214] In Table 1, Al:Si refers to the mass ratio of Al to Si in the second negative electrode active layer; Ti:Si refers to the mass ratio of Ti to Si in the second negative electrode active layer; and La:Si refers to the mass ratio of La to Si in the second negative electrode active layer.

[0215] Table 2

[0216]

[0217]

[0218] As can be seen from Tables 1 and 2, the battery of the present application embodiment has a lower K value, a lower room temperature full charge expansion rate, a lower high temperature full charge expansion rate, and a higher high temperature cycle capacity retention rate and room temperature cycle capacity retention rate. This indicates that by differentiating the first negative electrode active layer near the negative electrode current collector and the second negative electrode active layer far from the negative electrode current collector, the present application can improve the battery's room temperature and high temperature performance and reduce the battery's K value.

[0219] As can be seen from Examples 1 and 4-21, by further selecting the parameters of the negative electrode, positive electrode, and electrolyte, the high and low temperature performance of the battery can be further optimized and the K-value of the battery can be reduced while ensuring the energy density of the battery. Among them, the battery of Example 7 has a lower silicon content, so its K-value, high temperature cycling performance, and room temperature cycling performance are better than those of Example 1. However, as the silicon content decreases, the energy density of the battery also decreases.

[0220] Finally, it should be noted that other embodiments of the invention will readily occur to those skilled in the art upon consideration of the specification and practice of the invention disclosed herein. This invention is intended to cover any variations, uses, or adaptations of the invention that follow the general principles of the invention and include common knowledge or customary techniques in the art not disclosed herein, and is not limited to the precise structures described above and shown in the accompanying drawings, and various modifications and changes can be made without departing from its scope. The scope of the invention is limited only by the appended claims.

Claims

1. A negative electrode sheet, characterized in that, The negative electrode sheet includes a negative electrode current collector, a first negative electrode active layer, and a second negative electrode active layer; The first negative electrode active layer is located on at least one side surface of the negative electrode current collector, and the second negative electrode active layer is located on the surface of the first negative electrode active layer away from the negative electrode current collector; The first negative electrode active layer includes a first active material, which includes a first graphite; the second negative electrode active layer includes a second active material and a first solid electrolyte, which includes a second graphite and a silicon-carbon material. In the Raman spectrum, the first graphite is at a wavelength of 1530 cm⁻¹. -1 ~1590cm -1 Peak intensity I G With a wavelength of 1330cm -1 ~1390cm -1 Peak intensity I D The second graphite at a wavelength of 1530 cm -1 ~1590cm -1 Peak intensity I G 'With wavelength 1330cm -1 ~1390cm -1 Peak intensity I D 'Satisfy: I D / I G >I D ' / I G '; The silicon-carbon material includes spherical silicon-carbon material; all angles in the cross-section of the spherical silicon-carbon material are greater than 120°.

2. The negative electrode sheet according to claim 1, characterized in that, 0.2≤I D ' / I G ≤0.8; preferably, 0.2≤I D ' / I G ≤0.6; And / or, 0.2≤I D / I G ≤0.95; preferably, 0.3≤I D / I G ≤0.9; And / or, the Dv50 of the first graphite is 3-10 μm; And / or, the Dv50 of the second graphite is 8-20 μm; And / or, the mass percentage of silicon in the spherical silicon-carbon material is A, and the mass percentage of silicon-carbon material in the second active material is B, where 0.45 ≤ A / B ≤ 2.1; Preferably, A is 30%-70%; and / or, B is 20%-70%; Preferably, the silicon-carbon material comprises a porous carbon framework and silicon particles located in the pores of the porous carbon framework.

3. The negative electrode sheet according to claim 1 or 2, characterized in that, The first solid electrolyte includes at least one of Al, Ti, and La; Preferably, the first solid electrolyte comprises at least one of lithium aluminum titanium phosphate, lithium lanthanum titanate, and lithium lanthanum zirconium oxide. And / or, in the second negative electrode active layer, the mass percentage content of the first solid electrolyte is 0.1%-5%; Preferably, in the second negative electrode active layer, the mass ratio of aluminum to silicon is 0.03% to 0.15%. Preferably, in the second negative electrode active layer, the mass ratio of titanium to silicon is 0.4% to 2.1%; and / or, Preferably, in the second negative electrode active layer, the mass ratio of lanthanum to silicon is 0.05% to 0.4%.

4. The negative electrode sheet according to any one of claims 1-3, characterized in that, The spherical silicon-carbon material includes a silicon-carbon matrix and a carbon layer located on at least a portion of the surface of the silicon-carbon matrix; And / or, at least a portion of the surface of the spherical silicon-carbon material is coated with the first solid electrolyte, and the ratio of the Dv50 of the spherical silicon-carbon material to the Dv50 of the first solid electrolyte is 20 to 200; preferably, the ratio of the Dv50 of the spherical silicon-carbon material to the Dv50 of the first solid electrolyte is 20 to 107; preferably, the Dv50 of the spherical silicon-carbon material is 1 μm to 20 μm; preferably, the Dv50 of the first solid electrolyte is 10 nm to 1000 nm. And / or, the ratio of the porosity of the first negative electrode active layer to the porosity of the second negative electrode active layer is 1-1.9; preferably, the first negative electrode active layer includes a lithium replenishing agent; preferably, the lithium replenishing agent includes lithium powder.

5. The negative electrode sheet according to any one of claims 1-4, characterized in that, The surface of the second negative electrode active layer away from the negative electrode current collector has N first recesses, where N≥1; Preferably, the distance between two adjacent first recesses is 0.1 μm-5 μm; Preferably, the depth of the first recess is 0.1 μm-25 μm; Preferably, the first recess has a dimension of 20μm-200μm along the length of the negative electrode sheet.

6. A battery, characterized in that, Includes the negative electrode sheet as described in any one of claims 1-5.

7. The battery according to claim 6, characterized in that, It also includes a positive electrode sheet, which includes a positive current collector and a positive active layer located on at least one side surface of the positive current collector, the positive active layer including a second solid electrolyte; Preferably, the second solid electrolyte comprises at least one of garnet-type solid electrolyte, perovskite-type solid electrolyte, and sulfide solid electrolyte; preferably, the second solid electrolyte comprises at least one of lithium aluminum titanium phosphate, lithium lanthanum titanate, and lithium lanthanum zirconium oxide. Preferably, in the positive electrode active layer, the mass percentage of the second solid electrolyte is 0.01%-1%; The ratio of the Dv50 of the spherical silicon-carbon material to the Dv50 of the second solid electrolyte is 20 to 200; preferably, the ratio of the Dv50 of the spherical silicon-carbon material to the Dv50 of the second solid electrolyte is 20 to 107; preferably, the Dv50 of the second solid electrolyte is 10 to 1000 nm.

8. The battery according to claim 7, characterized in that, The positive electrode active layer further includes a positive electrode active material, which includes lithium cobalt oxide, and the lithium cobalt oxide includes an element M, which includes Y and / or La. Preferably, in the lithium cobalt oxide, the mass percentage of element M is 0.005%-0.6%.

9. The battery according to claim 7 or 8, characterized in that, The surface of the positive electrode active layer away from the positive electrode current collector has Q second recesses, where Q ≥ 1; Preferably, the distance between the center points of two adjacent second recesses is 100μm-2000μm; Preferably, the width of the second recess is 6μm-150μm; Preferably, the depth of the second recess is 3μm-25μm; Preferably, the battery has a wound structure, and the positive electrode sheet includes a straight section and a bent section along the winding direction. The positive electrode active layer of the bent section has Q' second recesses, where Q' ≥ 1.

10. The battery according to any one of claims 6-9, characterized in that, It also includes an electrolyte, which comprises fluoroethylene carbonate; Preferably, the electrolyte contains 5-18% fluoroethylene carbonate by mass; more preferably, the electrolyte contains 8-18% fluoroethylene carbonate by mass.